Analisis Pelaksanaan Pembelajaran Berorientasi Education for Sustainable Development (ESD) di Sekolah Dasar - Purnama, Vivi Amalia; Nurani, Dwi Cahaya (Universitas Indraprasta PGRI Jakarta, 2025)
The implementation of Education for Sustainable Development (ESD) in Elementary Schools faces several problems, which require deeper analysis for effective solutions. Many teachers do not understand the concept of ESD, so that in classroom learning the concept of ESD is not integrated and the minimal use of media or the environment as a learning resource which hinders the effective implementation of ESD in schools and limits students' awareness of the importance of sustainability. This study aims to analyze the implementation of ESD-oriented learning at SD Negeri 149 Palembang in 2024 using a descriptive qualitative method. Data were collected through observation and teacher interviews. The findings show that the school has carried out several activities that support the concept of sustainability such as carrying out mutual assistance activities, class pickets to maintain environmental cleanliness and carrying out market day activities on production and financial management. Also 50% of teachers understand the concept of ESD, but only 33.4% have succeeded in implementing it in learning. The main obstacles faced are the lack of information and teacher training related to the implementation of ESD-oriented learning and the curriculum that has not explicitly brought up the term ESD in learning outcomes. Although ESD has been implemented in several school activities, its implementation in learning at SD Negeri 149 Palembang still needs to be improved, especially in terms of strengthening teacher understanding, using ESD-based media, and integrating social and environmental issues system thinking in learning and curriculum. It is hoped that this study can provide recommendations to improve the implementation of ESD in elementary schools and form a generation that is more aware of the importance of sustainability.